A Labor Supply Elasticity Accord? - Ljungqvist, Lars; Sargent, Thomas J (American Economic Review, 2011)
A dispute about the size of the aggregate labor supply elasticity has been fortified by a contentious aggregation theory used by real business cycle theorists. The replacement of that aggregation theory with one more congenial to microeconomic observations opens possibilities for an accord about the aggregate labor supply elasticity. The new aggregation theory drops features to which empirical microeconomists objected and replaces them with life-cycle choices. Whether the new aggregation theory ultimately indicates a small or large macro labor supply elasticity will depend on how shocks and government institutions interact to put workers at interior solutions for career length.